Assessment of Dehydrogenase and Phosphatase Activities under Cotton-Wheat and Rice-Wheat Cropping Systems in Sangat Block of Bathinda District, Punjab - Brijesh Kumar Yadav and Sandeep Sharma, Pawandeep Kahlon* (Journal of the Indian Society of Soil Science, 2021)
Soils and their functions are critical for ensuring the provision of various ecosystem services. Soil enzymes activities were considered as an essential component of soil health, which can change due to anthropogenic activities, cropping practices and intensive land-use management systems. This study was conducted to estimate the changes in soil enzymatic activity under cotton-wheat and rice-wheat cropping systems in south-western Punjab, India. The soils under cotton-wheat system had higher dehydrogenase activity (DHA) of 49.17 µg TPF g-1 h-1 at 0-15 cm depth and 45.56 µg TPF g-1 h-1 at 15-30 cm depth compared with rice-wheat cropping system (47.81 µg TPF g-1 h-1 at 0-15 cm depth and 43.95 µg TPF g-1 h-1 at 15-30 cm depth). However, acid phosphatase (101.1-93.1 µg PNP g-1 soil h-1) and alkaline phosphatase (118.4-107.2 µg PNP g-1 soil h-1) activity was higher under rice-wheat cropping system than cotton-wheat cropping system (114.3-102.8 and 83.8-78.4 µg PNP g-1 soil h-1, respectively). Therefore, soil enzyme activities can be considered indicators of changes in restoration-induced soil quality and sensitivity to environmental factors and restoration practices.